Karakter Geotropisma Negatif pada Akar Tersembunyi Melaleuca leucadendra (L) L - Hanifa Marisa (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Marisa H. 2021. Negative geotrophism character of hidden root on Melaleuca leucadendra (L) L. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 872-877. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). An investigation had been done on the adventitious roots of Melaleuca leucadendra , last September 2020, at Tanjung Raya swamp side, Indralaya, Ogan Ilir Regency, South Sumatra Province, Indonesia. Direct measuring be done on the hidden under bark roots, by counting the number, size, growth ward, and branching character. It is found that 5 – 15 roots are exist on the trunk, about 0.5 – 2 m height , with maximum lenght is 60±6,78 cm, maximum size 6±0,65 mm diameter, and it is branched. Thirty three percents are growth upward (negative geotroph behavior). From this time and future, botanist could make notes, that a spesies has under bark branched roots and growth upward (negative geotropism ); M leucadendra.